Service Recovery Strategy in Private Hospitals: The Role of Experience, Symbolic, and Functional Brand Images - Siriyota, Kampanat; Chokpiriyawat, Thanuset (International Review of Management and Marketing, 2024)
This study investigates the influence of brand image on service recovery strategy, customer satisfaction, word-of-mouth communication, and revisit intentions within the context of private hospitals. The research identifies four dimensions of brand image: experiential, symbolic, functional, and social. The findings reveal that experiential, symbolic, and functional images positively impact service recovery strategy, while the social image does not have a significant positive effect. Service recovery strategies based on perceived justice significantly enhance customer satisfaction, which, in turn, fosters positive word-of-mouth and increases revisit intentions. The study highlights the importance of managing brand image to improve service recovery outcomes and maintain positive behavioral intention. Theoretical implications suggest further exploration of brand image factors and perceived justice in service recovery. Managerial implications emphasise the need for targeted marketing strategies that enhance functional and experiential brand images while avoiding social status associations. This study offers valuable insights for academia and practice, contributing to understanding and managing brand image and service recovery strategies in private hospitals.